ANALYSIS OF RESEARCH OF TECHNICAL EDUCATION IN SPECIFIC COUNTRIES - MASTALERZ, Elzbieta; BAGINSKA, Ludmila (Journal of Technology and Information Education, 2012)
The subject of educating young people in modern-day technology is important and disputed throughout many environments of today's world. This article presents the results of questionnaire research conducted in small groups of six countries' societies, comparing opinions on technical education and pragmatism of technical skills and knowledge.
Keywords: education; technology; pragmatism